THE EFFECT OF USING MOTHER TONGUE ON THE DEVELOPMENT OF COGNITIVE ABILITIES AND SECOND LANGUAGE IN EARLY CHILDHOOD - Simanjuntak, Kesmi Veronika; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2024)
This study aims to analyze the effect of using the mother tongue on the development of cognitive abilities and second language acquisition in early childhood. The use of the mother tongue during early childhood plays a crucial role in shaping children's cognitive and linguistic development, influencing their ability to acquire a second language. This research examines how the mother tongue serves as a foundation for cognitive processing, problem-solving, and the transfer of linguistic skills to a second language. Using a mixed-methods approach, the study involves observations, cognitive assessments, and language proficiency tests to explore the relationship between mother tongue usage and the development of bilingual abilities. The results indicate that children who actively use their mother tongue show enhanced cognitive flexibility and improved second language proficiency. Moreover, the study highlights strategies to optimize the integration of the mother tongue in early education, including creating bilingual learning environments, fostering cultural awareness, and engaging parents in the language development process. These findings are expected to contribute to educational practices that support cognitive and linguistic growth in young children.Keywords: Mother tongue, cognitive development, second language acquisition, early childhood education, bilingualism